2019
DOI: 10.1186/s12864-019-5807-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic and proteomic analysis of yellow shell and black shell pearl oysters, Pinctada fucata martensii

Abstract: Background The pearl oyster Pinctada fucata martensii ( Pfu. ), widely cultured in the South China Sea, is a precious source of sea pearls and calcifying materials. A yellow shell variety of Pfu. was obtained after years of artificial breeding. To identify differentially expressed genes between yellow shell and normal black shell pearl oysters, we performed transcriptomic sequencing and proteomic analyses using mantle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Another study found that hydrophobic amino acids were closely related to immunological activity [17]. At the same time, another study found that the mantle of Pinctada martensii contains a relatively rich total carotenoid content, which is also related to immunity [18]. This provides a nutritional and theoretical basis for SMPs to improve immunity during the inflammatory phase of skin wound healing and to produce an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that hydrophobic amino acids were closely related to immunological activity [17]. At the same time, another study found that the mantle of Pinctada martensii contains a relatively rich total carotenoid content, which is also related to immunity [18]. This provides a nutritional and theoretical basis for SMPs to improve immunity during the inflammatory phase of skin wound healing and to produce an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, during wound healing, proteins are being continuously synthesized, thus close attention towards nitrogen balance is required. SMPs, which are rich in glutamic acid, glycine (in pearl oyster mantle edge tissue, the most highly expressed genes had glycine-rich protein [18]), cysteine, and phenylalanine can achieve this nitrogen balance that is beneficial to angiogenesis, fibroblast proliferation, collagen synthesis, and wound remodeling [19]. Normal health and physiological functions require at least 20 vitamins and at least 16 minerals and trace elements [14].…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosinases are, for example, essential in the melanogenesis pathway as key regulators of melanin biosynthesis [ 33 ]. Tyrosinase deregulation has been reported in the bivalves C. gigas , P. yessoensis and P. fucata martensii, which show contrasting pigmentation phenotypes [ 13 , 34 , 35 ]. In bivalve molluscs, mantle tissue secretes proteins responsible for shell calcification and pigmentation, and pigments are probably formed in the secretory cells in the mantle and incorporated into the shell along the growing edge [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also these genes are involved in regulating all the other factors that regulate the colour of the nacre such as shell pigments and metal ions synthesis. In P. fucata , genes regulating calcium signalling, melanogenesis, phototransduction, rhodopsin metabolism and biomineralization was differentially expressed in the black and yellow phenotypes (Xu et al., 2019). In H. cumingii , genes related to the colour formation of the nacre layer, such as HcGIFLP1, HcCA2, HcCUBDC and Hc‐GIFLP2, were also identified (Luo, 2015).…”
Section: Pearl Colour Formationmentioning
confidence: 99%
“…Several multi‐omics studies have recently investigated molecular control of the production of coloured pearls with genes and transcription factors reported (Figure 2) and selective breeding processes to culture pearls of high economic value among others identified (Iwai et al, 2018; Ky et al., 2019; Xu, Huang, Shi, Zhang, & He, 2019). Although freshwater pearl productions are more suitable for studying pearl colour formation due to the longer pearl formation period than sea water pearls, this review combines both fresh and sea water pearls to provide a general overview and understanding for pearl colour formation.…”
Section: Introductionmentioning
confidence: 99%